Determination of optimal lot size using the Silver-Meal and Wagner-Whitin algorithms under the theory of constraints / Case study at Diyala Public Company - Kamel Jawad, Maha; Hassan Al-Obaidy, Omar Falah (Opción, 2019)
International companies are striving to reduce their costs in order to increase their profits, and these trends have produced many methods and techniques to achieve these goals. Of these methods what is judgmental and the other analog. The re- search seeks to adapt some of these techniques in Iraqi companies, and these tech- niques are to determine the optimal size of the batch using the algorithms of Sil- ver-Meal and Wagner-Whitin under the theory of constraints. The study adopted the case study methodology to objectively determine the size of the optimal batch of each of the products of the electronic scales laboratory in Diyala Company and in light of the bottlenecks in the work stations or restrictions that limit the energy. The results showed the ability to apply the theory of constraints by identifying the optimal mix that achieves the highest profit according to priority and its con- tribution to the treatment of the bottleneck by scheduling the production in light of the energy available in each workstation per month. The results also indicated the advantage of the Silver-Meal algorithm on the Wagner- Optimize the batch by adopting cost standards. Taking into account the recommendations of the research, which is the adoption of scientific methods in determining the size of the batch and the application of the theory of restrictions and re-internal arrangement of the laboratory and training employees to use these techniques to achieve the company the ability to reduce the cost and thus increase profits.